Dissecting the dynamics of the US trade balance in an estimated equilibrium model - Punnoose Jacob; Gert Peersman (National Bank of Belgium, 2012)
In an estimated two-country DSGE model, we find that shocks to the marginal efficiency of investment account for more than half of the forecast variance of cyclical fluctuations in the US trade balance. Both domestic and foreign marginal efficiency shocks have a substantial impact on the variability of the imbalance. On the other hand, while traditional technology shocks can generate counter-cyclical trade balance dynamics, they matter very little for the overall forecast variance.
Keywords: C11; F41; 330; Open Economy Macroeconomics; US Trade Balance; Investment Shocks; Bayesian Estimation of DSGE Models; Außenwirtschaftliches Gleichgewicht; Zwei-Länder-Modell; Neoklassische Synthese; Neue Makroökonomik offener Volkswirtschaften; Bayes-Statistik; Theorie; USA